2023
DOI: 10.1021/acsami.3c08119
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modulation via Conjugated Bithiophene Ammonium Salt for Efficient Inverted Perovskite Solar Cells

Xin Zhang,
Stijn Eurelings,
Andrea Bracesco
et al.

Abstract: The metal halide perovskite absorbers are prone to surface defects, which severely limit the power conversion efficiencies (PCEs) and the operational stability of the perovskite solar cells (PSCs). Herein, trace amounts of bithiophene propylammonium iodide (bi-TPAI) are applied to modulate the surface properties of the gas-quenched perovskite. It is found that the bi-TPAI surface treatment has negligible impact on the perovskite morphology, but it can induce a defect passivation effect and facilitate the charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The graph displays two distinct time regimes: the first, associated with trapassisted recombination, and the second, linked to carrier recombination at the interface. 37,38 The carrier recombination lifetimes obtained after fitting the TPV data are 46.82 ms for EtOH-treated, 48.62 ms for CB-treated, and 63.09 ms for DCBtreated PSCs, suggesting similar lifetimes for both EtOH and CB-treated devices. These results indicate that nonradiative charge recombination was minimized in the DCB-based solar cells compared to the other two.…”
Section: Resultsmentioning
confidence: 97%
“…The graph displays two distinct time regimes: the first, associated with trapassisted recombination, and the second, linked to carrier recombination at the interface. 37,38 The carrier recombination lifetimes obtained after fitting the TPV data are 46.82 ms for EtOH-treated, 48.62 ms for CB-treated, and 63.09 ms for DCBtreated PSCs, suggesting similar lifetimes for both EtOH and CB-treated devices. These results indicate that nonradiative charge recombination was minimized in the DCB-based solar cells compared to the other two.…”
Section: Resultsmentioning
confidence: 97%
“…Despite the rapid progress in research on single crystals of 3D HOIPs, , the amount of studies related to single crystals of 2D HOIPs remains comparatively limited, with the notable exception of 2D HOIPs containing phenethylammonium- and alkylammonium-based cations. However, recent reports have shown that extended aromatic systems can improve the efficiency and/or stability in thin-film devices . For example, carefully designed organic cations based on carbazole, pyrene, oligothiophene, or benzothienobenzothiophene have resulted in perovskite thin films with specific optoelectronic properties, such as improved charge carrier mobility ,, and lifetime. , Moreover, our research group and others have demonstrated the self-assembly of organic charge–transfer complexes into the organic layers of perovskite films by intercalating an acceptor chromophore into an organic layer containing electron donating organic cations, resulting in long-lived charge carriers and a reduced exciton binding energy . 2D HOIP single-crystal research with tailored aromatic moieties can therefore catalyze studies to ultimately maximize the figures of merit of various optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%